Diseño y construcción de un sistema mecánico para el monte y desmonte de ruedas de camión rin 22.5 (2025)
To perform preventive brake maintenance and change of grease to the bearings of a truck, two people They must remove the “dual”, which is the pair of wheels coupled, this has a weight of 250kg, for this each operator It is located on each side of the wheels, it has to be pulled until take it out, and then leave it on the side of the truck while it performs maintenance. If either of the two operators performs Improper movement risks injury lumbar. These injuries occur constantly in the assembly and disassembly of the “dual”, with this project we want change the way this work is currently done, to For this reason, a mechanism was developed that allows this task to be carried out safer way for operators